DIDACTIC PERSPIRATION IN SHANGHAI: EXPLANATORY THEORIES UNDERLYING A MODEL OF BEST PRACTICES - Jean Désiré BANGA AMVÉNÉ (Analele Universităţii din Craiova. Psihologie, Pedagogie, 2025)
Students in Shanghai, China, achieved the highest global scores in mathematics, science, and reading comprehension in the 2012 PISA assessment, outperforming education systems around the world. While this success is commonly linked to standardised socio-political factors such as severity, selective schooling or strong parental involvement, a television report explores the pedagogical factors behind these results. By analyzing the instructional approaches, methods and techniques highlighted in the video, this article argues that these Shanghai’s outstanding performance stems from behaviorist-inspired learning theories, emphasizing repetition and practice, within a framework referred to as "didactic perspiration."